Arnebia purpurea: a new member of formerly monotypic genus Huynhia (Boraginaceae-Lithospermeae) - Coppi, Andrea; Cecchi, Lorenzo; Nocentini, Daniele; Selvi, Federico (Phytotaxa, 2015)
The taxonomic position and affinities of the rare Turkish endemic Arnebia purpurea are analyzed using nuclear and plastid DNA sequence data and morphological characters. Phylogenetic analysis of a wide sample of old-world Lithospermeae consistently retrieved a clade with this species sister to Huynhia pulchra, the only member of the genus Huynhia. All other members of Arnebia s.l. (including Macrotomia) formed a separate clade subdivided in two lineages corresponding to the groups of the annual and the perennial species. Consequently, Arnebia does not appear monophyletic. Floral and palynological characters support the affinity of A. purpurea to Huynhia pulchra, in especially the stamens inserted at different heights in the corolla tube and the pollen grains with a single row of endoapertures along the equatorial belt. We therefore advocate the placement of A. purpurea in Huynhia and propose a new combination, implying that the latter is no longer a monotypic genus but includes two species with a sharply allopatric range in the Middle-East. Further studies with additional markers and a wider taxon sampling will help to elucidate relationships in Arnebia s.l..